The theme-topic interface : evidence from English - Gómez González, Ma. de los Ángeles (María de los Ángeles) (Pragmatics & beyond, 2001)
The Theme-Topic Interface (TTI) gives a useful catalogue of approaches to the concept Theme in the analysis of Natural Language. The book is written with both theoretical and descriptive goals and aims to synthesize andrevise current approaches to pragmatic functions. In addition, TTI explains that different thematic constructions in natural language reveal different discourse strategies related to point of view and speaker subjectivity, which shows the mutually supportive role of form and discourse function vis-á-vis each other. The book's value is enhanced by the use of natural languag.